2003
DOI: 10.1097/00063198-200309000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable states and central retinal vein occlusion

Abstract: Central retinal vein occlusion is a common cause of permanent visual loss. Work up and laboratory evaluation of patients requires the clinician to rule out hypertension, diabetes, hyperlipidemia, and glaucoma. Patients without an identifiable risk factor are often subject to extensive testing for primary and secondary thrombophilias. The purpose this paper is to review the literature to determine which of these tests is associated with central retinal vein occlusion. Antiphospholipid antibodies and elevated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
2
23
2
4
Order By: Relevance
“…214 Moreover, retinal venous and arterial occlusions are known to be associated with hypertension, diabetes mellitus and hypercoagulability or hyperviscosity syndromes. 122,157,162,214 In addition to the known associations of obesity with hypertension and diabetes, several reviews have presented some evidence supporting the association of hypercoagulability disorders with obesity and metabolic syndrome. 3, 151 This provides further support for the possible association between obesity and retinal vascular occlusive diseases.…”
Section: Obesity and Other Eye Diseasesmentioning
confidence: 99%
“…214 Moreover, retinal venous and arterial occlusions are known to be associated with hypertension, diabetes mellitus and hypercoagulability or hyperviscosity syndromes. 122,157,162,214 In addition to the known associations of obesity with hypertension and diabetes, several reviews have presented some evidence supporting the association of hypercoagulability disorders with obesity and metabolic syndrome. 3, 151 This provides further support for the possible association between obesity and retinal vascular occlusive diseases.…”
Section: Obesity and Other Eye Diseasesmentioning
confidence: 99%
“…On individual examination of each of these, 36 fitted the inclusion criteria for tHcy. 10 -12,17-24,27,28,30,32,40 -60 The remaining 11 articles were meta-analyses, 7,16 review articles, 61 commentaries/ letters, 62,63 case reports, 64 -69 or series. On closer examination, 2 articles were duplicate publications of the same dataset, 48,57 whereas a further 9 articles did not present the data in a suitable format that could be used for meta-analysis, 41,42,46,47,49 -51,55,56 for example, presenting the tHcy data as percentage of the population with elevated levels 41,42,50 or not reporting tHcy concentrations or variance in a control groups.…”
Section: Total Homocysteinementioning
confidence: 99%
“…Among the parameters tested, hyperhomocysteinemia (HHcys) and circulating antiphospholipid antibodies are reported to be significantly more common in the patients with CRVO [3]. Boyd et al [4] have reported that there is no significant increase in factor VIII (von Wilbrand factor), apart from homocysteine (Hcys) levels in the CRVO cases compared with the control subjects.…”
Section: Introductionmentioning
confidence: 99%